Effects of selected probiotics on the growth, survival and gastro-intestinal bacterial population of juvenile giant freshwater prawn (Macrobrachium rosenbergii, de man) - Ramzani, Sara Ravan (2011)
Two experiments were carried out in this project. The first study was done to determine the effectiveness of putative bacteria as a probiotics for growth enhancement and survival of juvenile Macrobrachium rosenbergii and protection against Aeromonas hydrophila challenge. A total of 360 juveniles M. rosenbergii were individually weighed and kept in twenty one 60 L aquaria. Four treatments were conducted as follows; T1 (Control group), T2 (B. subtilis), T3 (Lactobacillus acidophilus) and T4 (Commercial probiotic bacteria). The final concentration of the probiotic bacteria in the treated feeds was set at 8 × 109 CFU/g feed. All prawn treated with probiotic-supplemented diets wed better growth performances and feed utilization as compared to those in the control fed with basal diet. The higher growth parameter and survival rate of the prawns fed with B. subtilis–added diets over the control feed indicated the probiotic-ability of the B. subtilis. There was a significant different (P<0.05) in weight gain, specific growth rate, feed intake and FCR between the treated and control tanks. The prawns fed with the control diet with no addition of bacteria, recorded the lowest feed intake. Tthe best FCR value (2.56 ± 0.09) was derived from the juvenile fed diet containing B. subtilis. After 60 days of comparison among putative B. subtilis, Lactobacillus acidophilus, commercial probiotic bacteria and probiotic free diets in juvenile M. rosenbergii, there was no significant difference (P > 0.05) in biochemical composition between groups treated putative B. subtilis and Lactobacillus acidophilus and commercial probiotic treated groups. There was significant difference between groups receiving putative B. subtilis, Lactobacillus acidophilus and commercial probiotic bacteria diets in growth enhancement of juvenile M. rosenbergii. This study indicated the increase in the growth and survival of the treated prawns, with reduced mortality as compared to the control group. The second study was conducted to determine the effects of periodical application of probiotics and pathogenic effects of A. hydrophila on the survival and growth enhancement of juvenile M. rosenbergii with a total of 840 M. rosenbergii post-larvae procured from Center of Marine Science (COMAS), Port Dickson, UPM. These prawns were individually weighed and kept in twenty one 60 L aquaria. Two trials were carried out. The first trial had seven feeding regimes designed as: T1 (Control group); T2 (B.subtilis bacteria once every day), T3 (B. subtilis once every 5 day), T4 (B. subtilis once every 10 days), T5 (Commercial Probiotic (CP) once every day), T6 (CP once every 5 days) and T7 (CP once every 10 days). The final concentration of the probiotic bacteria in the feeds was determined at 8 × 109 CFU/g feed. After 60 days of feeding, the prawns in each treatment were measured for growth performance. Then the prawns in each treatment were challenged with A. hydrophila at 107 CFU/mL for 21 days, and measurements for growth and survival rates were recorded at end of the challenge experiment. Parameters such as histopathology, bacteriological study, growth measurement and water quality were taken. Significant differences (P< 0.05) in weight gain, specific growth rate, feed intake and FCR between the treated B. subtilis and control groups were observed. Results showed a significant difference between control and treatments in the log of Bacillus count (Control: Mean = 1.40 ± 0.03, CPF; Mean= 4.10 ± 0.064, PF; Mean = 3.46 ± 0.084) and the log of gram negative count (Control; Mean= 3.29 ± 0.08, CPF; Mean = 1.91 ± 0.045, PF; Mean = 2.22 ± 0.059) (P < 0.001). Appropriate probiotic applications have been shown to improve intestinal microbial balance, thus leading to improved food digestion, and reduced pathogenic bacteria multiplication problems in the gastrointestinal tract.